Using a Stages Model to Reveal the Politics in the Health Policy Process; Comment on "Modelling the Health Policy Process: One Size Fits All or Horses for Courses?" - Rod Sheaff (Kerman University of Medical Sciences, 2023)
Models of the health policy process have largely developed in isolation from political studies more widely. Of the models which Powell and Mannion's editorial considers, a stages model of the policy process offers a framework for combining these specifically health-focused models with empirical findings and more general explanatory models of the policy process drawn from other political studies. This commentary uses a stages model to assemble a bricolage which combines some of these components. That identifies a further research task and suggests ways of revealing in more life-like ways the politics involved in the health policy process: that is, how that process channels wider, often conflicting, non-health interests, actors, policies, conflicts, ideologies and sources of power from outside the health system into health policy formation, and introduces non-rationality.